Analgezie u porodu v České republice v roce 2011 z pohledu studie OBAAMA-CZ- prospektivní observační studie - Štourač, P; Bláha, J; Nosková, P; Klozová, R; Seidlová, D; Jarkovský, J; Zelinková, H; Skupina, Obaama-Cz Studijní (Ceska gynekologie, 2015)
GOAL OF THE STUDY: The aim of national survey was to describe current practice for analgesia during labour provided by anaesthesiologists in the Czech Republic (CZE). TYPE OF THE STUDY: National prospective observational. SETTING: 49 obstetric departments in CZE. METHODS: We aimed to enrol all 97 obstetric departments in CZE and to monitor every case of anaesthetic care in peripartum period during November 2011. Data were recorded to Case Report Form with two parts (Demography 2010 and Case Report) into TrialDB database (Yale University, USA; adapted IBA, MU, CZE). Demographic data for CZE were obtained on request by ÚZIS. The data were analysed using SPSS 22. RESULTS: We enrolled 1943 cases of anaesthesiological care and 579 (29.8%) of them was to relief labour pain. Population and center weighted estimate of incidence of epidural labour analgesia was 12.5% (95% CI: 10.6% - 14.4%). Epidural analgesia was the most frequently applied via Tuohy needle G18 (97.8%), with administration of an epidural catheter G20 (95.7%), via medial approach (98.8%), in lateral position (76.7%) by the loss of resistance method (94.3%). All administrations of epidural analgesia were started by initial bolus, only in 28.2% of cases were followed continously. Always has been applied mixture of local anaesthetic with sufentanil at a dose of 3-10 mcg. Bupivacaine was most frequently used local anaesthetic (80.7%), followed by levobupivacaine (12.6%). Median concentrations both bupivacaine and levobupivacaine were 0.125% (min. 0.1%, max. 0.3%).The most common complication of epidural analgesia was repeated puncture (21.2%), blood in the catheter (1.4%), blood in the needle (1.2%), unintended puncture of the dura mater (0.7%) and transient paresthesias (0.5%). CONCLUSION: In comparison to previously published data there was trend for lower incidence of epidural analgesia for labour in the CZE.
Keywords: Analgesia, Epidural; Analgesia, Obstetrical; těhotenství; national survey; Česká republika; výsledek těhotenství; labour analgesia; Prospective Studies; sufentanil; Czech Republic; Bupivacaine; Pain Measurement; měření bolesti; epidural analgesia; levobupivakain; porodní děj; Czech Republic.; bupivakain; ženské pohlaví; Sufentanil; programy národního zdraví; prospektivní studie; Anesthetics, Local; Humans; Pregnancy; Pregnancy Outcome; Labor, Obstetric; porodnická analgezie; National Health Programs; epidurální analgezie; anestetika lokální; Female; Levobupivacaine; lidé